1936
DOI: 10.1021/ja01297a021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfuric Acid Concentration upon Reaction between Olefins and Benzene

Abstract: Sulfuric Acid in the Olefins-Benzene Reaction 919 Experiment 2.-The liquid product was separated in the following fractions: (1) 67-82°, 58.0 g.; (2) 152-153°, 10.0 g.; (3) 168-170°, 5.5 g.; (4) bottoms, 4.0 g. Fraction 2 was isopropylbenzene as shown by its analysis for carbon and hydrogen, molecular weight and conversion to benzoic acid by oxidation with permanganate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1943
1943
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…PPFcPM synthesized using sulfuric acid as the catalyst resulted in toluene inclusion due to Friedel‐Craft alkylation 23. The influence of temperature and catalyst was also observed in all of the one step azeotropic distillation scenerios, thus providing a system which has the ability to be adjusted.…”
Section: Resultsmentioning
confidence: 97%
“…PPFcPM synthesized using sulfuric acid as the catalyst resulted in toluene inclusion due to Friedel‐Craft alkylation 23. The influence of temperature and catalyst was also observed in all of the one step azeotropic distillation scenerios, thus providing a system which has the ability to be adjusted.…”
Section: Resultsmentioning
confidence: 97%
“…In Figure 3 the ortho acid rate remains nearly constant from 35,No. In Figure 3 the ortho acid rate remains nearly constant from 35,No.…”
Section: Ohsosmentioning
confidence: 91%
“…Table 475 gives an idea of the procedure when sulphuric acid is used as catalyst. Consumption of acid in kg per kg alkylate [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Molar ratio of benzene to propene tetramer 3-5:1 Residence time, in hours 1 Ratio of acid to hydrocarbon 1:1 Oil-soluble high-molecular-weight salts of alkylarylsulphonates are used extensively as additives to motor lubricating oils. They are made from suitable lubricating oil fractions by sulphonation with oleum or "Sulfan".…”
Section: A the Alkylation Of Benzene With Propene Polymerizate In Thmentioning
confidence: 99%
“…More recently, this procedure has been subjected to a detailed scientific and practical investigation [3]. It is used today particularly for the large scale industrial manufacture of ethylbenzene.In 1895, RADZIEWANOWSKY [4] obtained eumene (isopropylbenzene) in the same way by the action of propene on benzene in the presence of anhydrous aluminium chloride.Later, BROCHET [5] found that mineral acids act as catalysts in the alkylation of aromatic hydrocarbons.IPATIEFF et al [6] showed that sulphuric acid, for example, was capable of catalysing the reaction between benzene and pentene, with the production of mono-, di-, and triamylbenzenes in good yields. Propene and the butènes [7] react equally readily, while benzene cannot be alkylated to an alkylbenzene with ethylene in the presence of sulphuric acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation